Morphometric Study of Sub Axial Cervical Spine Pedicles in Nepalese Population - Baral, Yadu nath; Thapa, Shrawan Kumar; Marasini, Rudra Prasad; Paudel, Srijana; Gurung, Subash; Ghimire, Kathit raj; Yadav, Rajesh Kumar; Baral, Sushila (Journal of Nepal Health Research Council, 2023)
Background: Mal-positioning of cervical screws risks neurovascular injury so, it is necessary to understand cervical pedicle morphology for pedicle screw fixation in the region. The risks of pedicle screw insertion in the cervical spine can be mitigated by a three-dimensional appreciation of pedicle anatomy. The study aims to determine the morphology of the sub axial cervical spine pedicles in Nepalese Population based on computerized tomography. Methods: A cross-sectional study using computerized tomography scans of the spine was made among the randomly selected 87 patients who had visited National Trauma center, Kathmandu, Nepal with vertebral fracture other than cervical vertebrae. Patient was examined as per Advanced Trauma Life support protocol and neurological assessment. Measurement was done from the third cervical vertebra down to the seventh cervical vertebra in computer with standard software in the department of radiology from where all the computerized tomography scan reporting are done. Results: The mean pedicle length ranged from 4.41 mm at C3 to 4.96 mm at C7 where mean pedicle height ranged from 4.64 at C3 to 5.12 at C7. Pedicle length, pedicle height and pedicle width were observed to be statistically significant with gender. The pedicle axial length of C3 and C7 vertebra were found significant with gender. All parameters were found to be greater in male compared to female. Conclusions: The study revealed that pedicle length, pedicle height, pedicle width, pedicle axial length increased from third to seventh cervical however, transverse angulation increased up to fifth vertebra and decreased to seventh vertebra.Keywords: Morphology; sub-axial cervical spine; tomography.